Marketing and Brand Design of Destination Experiences: The Role of ICT - Agapito, Dora; Lacerda, António (Journal of Tourism, Sustainability and Well-being, 2014)
The proliferation of Information and Communication Technologies (ICT) with particular emphasis on internet have been rapidly adapted to tourism, where new opportunities for design and marketing strategies for destinations are being explored in both physical and virtual environments. Furthermore, the process of designing strong brands and facilitating positive and memorable experiences are central activities concerning destinations aiming to become more competitive. Accordingly, Destinations Marketing Organizations (DMOs) are now exploring ICT and new forms of human interactions with a view to offer new opportunities for visitors to engage in the process of co-creating enhanced destination experiences in a technology-based environment. Considering that ICT both contribute to the process of designing innovative destination experiences and support enhanced individuals’ experiences before, during and after the trip, the purpose of this paper is to explore the role of ICT in the marketing and brand design of destination experiences.